A mechanical system for harvesting, in-field collecting and in-field transporting of oil palm fresh fruit bunches - AlJawadi, Rafea Abdulsattar Mohammed (2018)
Malaysia is the second leading palm oil producing country in the world. The industries are confronted with several challenges that hinder the oil palm extraction rate, such as lack of skilled man-power, and ineffectiveness of the manual harvest and in-field collection and transporting techniques adopted currently for oil palm fresh fruit bunches (FFB). The conventional method, deploys human harvester ranging from an average number of five personnel per team (harvester), working for eight hours a day. Hence, reducing the daily productivity of the industries based on the limited available raw material (FFB), which in turns affects the productivity, and turnover of the oil palm industries. These challenges motivated the design, and fabrication of a machine system, that could harvest, and in-field collect and transport all the cut oil palm FFBs. The first approach, proposed the design, and fabrication of a pneumatic Cantas with a pole length of 3m, air screw driver on 6.3 bar, single stage pump air compressor, that is powered by 3.73 kW gasoline engine. This designed machine operated at 280 l.min- 1 for cutting of fronds, and FFBs by the attached sickle. The second approach was the design, and fabrication of a flexible Cantas with pole of 3 m, powered by a 0.97 kW gasoline engine, and operated with a six joint pieces of flexible drive shaft (FDS) totalling 6 m long between the engine and the pole. A gearbox that converts rotary motion to operate the cutting sickle was attached alongside with a frond supporting mechanism at the end of the pole, to ease the cutting operation during harvest. A 140 kg lifting capacity hydraulic crane of 7 meters height, with five degrees of freedom, and operated by Power Take OFF (PTO) from the tractor was fabricated to catch the cut FFBs and transport the FFBs to the collecting point. A hexagonal diamond shaped collector-basket was developed at the end of the crane for holding the FFBs in position during harvesting operation. The transitional movement of the mechanical systems was able to harvest five FFBs for 193.48 - 247.00 seconds. It took 641.76 - 666.17 seconds for harvesting, collecting, and in-field transporting of five FFBs to unload at the end of harvesting line. This operation for the total harvesting and transporting FFBs productivity increased by 66.63 - 73.36 % when compared to manual harvesting tool. This concept of harvesting managed to eliminate the loading time of loose fruits when FFB falls to the ground. Thus the average total number of FFBs harvested, collected, and in-field transported were 28.082 to 27.099 FFB.hr-1 at both FFB heights of 2-3 and 3-4 meters, compared to 17.383 to 12.723 FFB.hr-1 under the manual system. The results from both machine designs, and fabrications introduced a novel automated harvesting and transporting of the FFBs, whereby showing a reduction in the number of required unskilled work force to two personnel (the Cantas operator or harvester, and the tractor driver as the crane operator) as against three currently used. The research achieved in developing an integrated harvesting, collecting, and transporting machine which includes the design and fabrication of the crane harvester, the collector-basket , the modified flexible hose with frond support for modified Cantas and the new pneumatic Cantas. The concept of this integration adopted was to enable the harvesting, collecting, and transporting operations in a single passage, thus eliminating the activities of loading FFBs into the trailer and collecting the loose fruits.